Low temperature, mechanical wound, and exogenous salicylic acid (SA) can stimulate the SA signaling molecule as well as its downstream pathway and the formation of fruiting bodies in Flammulina filiformis - Li, Ziyan; Wen, Jin; Jing, Zhuohan; Li, Hui; Huang, Jiahua; Yuan, Chengjin; Xian, Lijun; Gao, Lingling; Zhu, Jian; Xie, Baogui; Tao, Yongxin (Frontiers in Microbiology, 2023)
Low temperature (LT) and mechanical wound (MW), as two common physics methods, have been empirically used in production to stimulate the primordia formation of Flammulina filiformis, which is typically produced using the industrial production mode. However, the detailed effect on the fruiting body formation and important endogenous hormones and signaling pathways in this process is poorly understood. In this study, LT, MW, their combination, i.e., MW + LT, and low concentration of SA (0.1 mM SA) treatments were applied to the physiologically mature mycelia of F. filiformis. The results showed that the primordia under the four treatments began to appear on the 5th−6th days compared with the 12th day in the control (no treatment). The MW + LT treatment produced the largest number of primordia (1,859 per bottle), followed by MW (757), SA (141), and LT (22), compared with 47 per bottle in the control. The HPLC results showed that the average contents of endogenous SA were significantly increased by 1.3 to 2.6 times under four treatments. A total of 11 SA signaling genes were identified in the F. filiformis genome, including 4 NPR genes (FfNpr1-4), 5 TGA genes (FfTga1-5), and 2 PR genes (FfPr1-2). FfNpr3 with complete conserved domains (ANK and BTB/POZ) showed significantly upregulated expression under all four above treatments, while FfNpr1/2/4 with one domain showed significantly upregulated response expression under the partial treatment of all four treatments. FfTga1-5 and FfPr1-2 showed 1.6-fold to 8.5-fold significant upregulation with varying degrees in response to four treatments. The results suggested that there was a correlation between “low temperature/mechanical wound—SA signal—fruiting body formation”, and it will help researchers to understand the role of SA hormone and SA signaling pathway genes in the formation of fruiting bodies in fungi.